ANALISIS KEMAMPUAN BERPIKIR REFLEKTIF SISWA SMP DITINJAU DARI DISPOSISI MATEMATIS SISWA - Yuni Hajar; Ridwan Yanwar; Aflich Yusnita Fitrianna (IKIP Siliwangi, 2018)
Reflective thinking ability and mathematical disposition in mathematics learning is very important to be improved. Reflective thinking ability can help students to get more optimal learning outcomes and mathematical disposition is required by students to solve a mathematical problem. The purpose of this study is to analyze the difficulties faced by junior high school students in working on the problem of reflective thinking ability that review based on students' mathematical disposition ability. The research method used is descriptive analysis method to analyze the available data and processed so as to obtain a clear description of the facts and the relationship between the phenomena studied. The sample in this research is the students of class IX B in SMPN 5 Cimahi. The results of this study is that almost allindicators ofreflective thinking abilityare still not achieved review bases on student’smathematical disposition. this is due to the following factors : (a) mathematic material that is still poorly understood so that students have difficulty when solving difficult mathematical problems ; (b) student made a mistake in concept when do reflective thingking ability test; (c) the student has never experienced a test with reflective thinking ability before.